Yield, phenology and triterpene saponins in Colombian quinoa - Manjarres Hernández, Elsa Helena; Morillo Coronado, Ana Cruz; Cárdenas Chaparro, Agobardo; Merchán López, Claudia (Frontiers in Sustainable Food Systems, 2022)
Exploring yield, phenology and their relationship with secondary metabolites in seeds provides a fundamental analysis that expands knowledge on the nutritional quality of seeds and the effect on productive potential. This knowledge is fundamental when improving or selecting nutritionally important crops, including Chenopodium quinoa Willd, which has excellent nutritional properties and contributes to global food security. This species contains saponins, a metabolite that imparts a bitter taste and can be highly toxic to consumers in large quantities. Therefore, the identification and selection of genotypes according to their saponin contents and outstanding agronomic characteristics are fundamental objectives for the genetic improvement programs of these species. Therefore, the objective of this research was to evaluate the characteristics of the grain, the phenology and the saponin content of 30 C. quinoa accessions with an aim to select or relate genotypes according to their yield and grain quality. The accessions were sown using randomized complete blocks (RCB) with nine repetitions for each material. Seven FAO-defined descriptors were evaluated to characterize the grain and physiological maturity. Saponin was extracted using microwave, and the quantification was done with high-performance liquid chromatography (HPLC) which a UV-VIS detector at 277 nm wavelength. The accessions were classified according to their phenology: semi-late (56.7%), late (36.7%), and semi-early (3.3%). The total triterpene saponin content varied from 0.018 to 0.537%. The multivariate and cluster analyses formed groups of accessions with good yields (>62.02 g of seeds per plant) and desirable grain morphological characteristics. The more suitable accessions for the production of saponins are Quinoa semiamarga (0.537%), Quinoa peruana (0.412%) and Amarilla de maranganí (0.305%). Quinoa real and Quinoa primavera are more suitable for food products, which can be used as parents in future quinoa genetic improvement programs in Colombia.